Estimating economic capital for operational risk - Domantay, Vernalin Grace F.; Sy, Polly W. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2009)
According to Basel II, estimating the economic capital for operational risk is as important as estimating the economic capital for market and credit risk since it provides integration and better management of operational risk. The estimation of the economic capital should consider only the unexpected operational losses according to Robert A. Jarrow. The Loss Distribution Approach (LDA) together with Jarrow's statement was used to quantify the economic capital of a local bank in this study.
Thesis (M.S. Applied Mathematics)--University of the Philippines Diliman
Keywords: Corporations -- Investor relations; Stocks -- Marketing; Stocks -- Prices; Economic value added; Risk assessment